2016
DOI: 10.1002/nbm.3668
|View full text |Cite
|
Sign up to set email alerts
|

The clinical utility of QSM: disease diagnosis, medical management, and surgical planning

Abstract: Quantitative susceptibility mapping (QSM) is an MR technique that depicts and quantifies magnetic susceptibility sources. Mapping iron, the dominant susceptibility source in the brain, has many important clinical applications. Herein, we review QSM applications in the diagnosis, medical management, and surgical treatment of disease. To assist in early disease diagnosis, QSM can identify elevated iron levels in the motor cortex of amyotrophic lateral sclerosis patients, in the substantia nigra of Parkinson's di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
91
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(94 citation statements)
references
References 138 publications
(186 reference statements)
3
91
0
Order By: Relevance
“…Quantitative susceptibility mapping (QSM) is an emerging MRI technique that can reveal disease‐related changes in tissue iron, myelin and calcium content, and venous oxygenation. Therefore, QSM shows potential for an increasing range of clinical applications . Magnetic susceptibility (χ) is an intrinsic tissue property relating the magnetic field induced within the tissue to the applied magnetic field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative susceptibility mapping (QSM) is an emerging MRI technique that can reveal disease‐related changes in tissue iron, myelin and calcium content, and venous oxygenation. Therefore, QSM shows potential for an increasing range of clinical applications . Magnetic susceptibility (χ) is an intrinsic tissue property relating the magnetic field induced within the tissue to the applied magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, QSM shows potential for an increasing range of clinical applications. 1 Magnetic susceptibility (χ) is an intrinsic tissue property relating the magnetic field induced within the tissue to the applied magnetic field. The relationship of χ (r), the tissue susceptibility distribution over space (r), to the resulting phase variations (φ (r)) can be expressed by the following convolution with the dipole field distribution (d (r)) where B 0 denotes the main magnetic field 2,3 :…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, our data demonstrated that the increased copper levels in the cortex and cerebellum may contribute to impairments in movement behavior and locomotor activity. QSM is a post-processing technology that uses a high pass filter phase image to distinguish between the influences of paramagnetism and diamagnetism on susceptibility-weighted imaging signals (Eskreis-Winkler et al, 2017). QSM has been used in several studies to quantify iron or copper levels in patients with WD (Fritzsch et al, 2014;Dusek et al, 2017Dusek et al, , 2018Saracoglu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Furthermore, R 2 * measurements cannot differentiate between para-and diamagnetic structures. 15 Recently, QSM [15][16][17] has been investigated as an alternative method for quantifying BMD, with promising initial results. 18,19 Dimov et al showed that susceptibility values were closely correlated with CT measurements of BMD in a porcine hoof, and were able to generate susceptibility maps in which cortical bone was homogenous and diamagnetic, as expected from theory.…”
Section: Introductionmentioning
confidence: 99%